Adultery and Rape in the Muslim Criminal Law: Comparative Law Analysis - MANNA, Ammar Abdul Karim; MURKSHTIS, Maryus Yokubo; BERTOVSKIY, Lev Vladimirovich; SELEZNEVA, Natalya Aleksandrovna; IGNATOVA, Milena Alekseevna (Journal of Advanced Research in Law and Economics; Vol 8 No 1 (2017): JARLE Volume VIII Issue 1 (23) Spring 2017, 2017)
In the Muslim world countries the marriage relationships are paid special attention to. Religious views of the Muslims deny any sexual intercourse before the marriage, and after the official marriage the adulterous intercourse (widely known as adultery) is punished by the criminal law. In many countries of the world the adultery is not considered to be a felony since it concerns the personal sphere of a human life where the state can't interfere with any reason. The lack of practice in prosecution for the adultery in the European countries makes the specified topic of particular interest.